Coexistence of Tubercular Lymphadinitis and Pleural Effusion - A Rare Presentation - Chowdhury, A; Hoque, M; Shaheeduzzaman, M; Rokonudidn, M; Chawdhury, NA; Islam, SM Monowarul (Anwer Khan Modern Medical College Journal, 2012)
Tuberculosis (TB) is a prevalent systemic bacterial infection caused by Mycobacterium tuberculosis. In this article we are reporting a patient with bilateral pleural effusion and left sided neck swelling. Histopathologyof thc neck swelling diagnosed the case as tubcrculous lymphadcnopathy. Thorough investigation revealed no evidence of primary tuberculosis elsewhere, the patient improved dramatically within one month of `4 drugs combination of anti-tubercular therapy. The patient was asked to continue treatment till the prescribed period. There are limited global reports on the coexistence of tubercular lymphadenitis and pleural effusion and possibly this is the first case study from Bangladesh. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10112 AKMMCJ 2012; 3(1): 31-33